FRI0572 Prevalence of echocardiographic findings in connective tissue diseases – a retrospective cohort study. (12th June 2018) - Weiss, K.; Schmidt, W.A.; Krause, A.; Schäfer, V.S.
Abstract : Background: Echocardiography is routinely performed in patients with connective tissue diseases (CTD), mostly to evaluate cardiac involvement or development of pulmonary arterial hypertension (paH). Despite its frequent application there is incomplete data for the range and frequency of findings. Objectives: 1) To study the frequency of echocardiographic findings in routinely examined patients with different CTD. 2) To report which findings were associated with a history of inflammatory cardiac involvement. 3) To analyse whether findings changed over time in patients with several examinations. Methods: Retrospective chart review of all consecutive patients from a tertiary rheumatological referral centre with CTD diagnosis and echocardiographic examination between 01/01/2006 and 31/12/2015. For each echocardiographic finding, the proportion of patients per diagnosis with a pathological result in at least one examination was calculated. Each finding's frequency was compared between patients with and without previously documented inflammatory cardiac involvement; p<0.05 in Fisher's exact test was considered significant. For patients with more than one visit, we recorded how often findings developed or resolved between two consecutive examinations. Results: 1004 patients with different CTD and a total of 1660 performed echocardiographies were analysed. Table 1 displays the frequency of findings in the whole cohort and for each CTD. The following findings were significantly more common in patients with known inflammatory cardiac involvement (n=109) than in those without (n=896): regurgitation of tricuspid valve (45.0% (n=49) of patients with cardiac involvement vs. 23.2% (n=206) of patients without, p<0.001) and of pulmonary valve (15.6% (n=17) vs. 6.1% (n=54), p=0.001); global hypokinesia (3.7% (n=4) vs. 0.4% (n=4), p=0.007); dilatation of left atrium (33.9% (n=37) vs. 17.5% (n=156), p<0.001), of left ventricle (LV) (11.0% (n=12) vs. 5.1% (n=45), p=0.025), of right atrium (15.6% (n=17) vs. 1, 7% (n=15), p<0.001) and of right ventricle (15.6% (n=17) vs. 1.9% (n=17), p<0.001); signs of paH (28.4% (n=31) vs. 5.3% (n=47), p<0.001), and pericardial effusion (43.1% (n=47) vs. 6.5% (n=58), p<0.001). 314 patients had consecutive examinations; medium interval between first and last examination was 40 months (SD: 28, range: 0.9–115). New development or resolution of findings between consecutive examinations was common. The findings which most commonly developed were mitral valve regurgitation in 24% (n=76) of patients, tricuspid regurgitation in 21% (n=67), aortic valve sclerosis in 18% (n=55) and LV dysfunction in 20% (n=62). The findings which most commonly resolved were mitral regurgitation in 15% (n=47) of patients, tricuspid regurgitation in 16% (n=49), aortic valve sclerosis in 10% (n=31) and LV dysfunction in 13% (n=42). Conclusions: Echocardiographic examinations frequently revealed structural and/or functional abnormalities in patients with CTD. Some findings were associated with previous cardiac involvement and might be disease-related. When reevaluating a patient, findings had often newly developed or resolved since the last examination. Overall, repeated echocardiographic examinations may be a valuable part of follow-up in CTD patients. Acknowledgements: We thank Bernd Schicke for his assistance with statistical analyses. Disclosure of Interest: None declared